Cost and technology readiness level assessment of emerging technologies, new perspectives, and future research directions in H2 production. Issue 19 (7th September 2022) - Khan, Saleem Nawaz; Yang, Zhu; Dong, Weiguo; Zhao, Ming
Abstract : This review provides a cost and technology readiness level assessment of emerging technologies in H2 production and overview of future research directions. Abstract : There is a worldwide debate on the use of renewable energy resources and economically viable technologies for energy-efficient systems. Since H2 energy is the future of the world energy scheme, at the center of the discussion are the old existing methods of research and some new developments in emerging technologies. The few currently used H2 production technologies are outdated and not so competitive and this means a tight bottleneck in the overall energy system. Furthermore, expectations arise with the advancement of the world energy system to find the most innovative alternative renewable energy resources. This present review allows a better understanding of conventional technologies and recently emerging techniques for H2 production. This paper provides a brief introduction to some of the existing technologies/methods, advantages, and drawbacks. Furthermore, this work aims to show the new state-of-the-art emerging technologies and their benefits in the future energy system and a clear pathway to finding alternative schemes of energy with better working efficiencies. Most importantly, the maturity level of most fossil-based technologies and the new emerging technologies based on the timeline for their commercial availability is a part of this review. Cost and technology readiness level assessment of some of the old and new emerging technologies for unit H2 production in comparison with or concerning commercially available steam methane reforming technology has been summarized. Future perspectives and new research directions in H2 production technology have also been proposed for further research and development.